2013
DOI: 10.1308/003588413x13511609958451
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the healing of the perineum following surgery

Abstract: North West London Hospitals NHS Trust, UK aBStract INTRODUCTION The aim of this study was to establish patient and procedural factors associated with the development of an unhealed perineum in patients undergoing a proctectomy or excision of an ileoanal pouch. METHODS A review of 194 case notes for procedures performed between 1997 and 2009 was carried out. All patients had at least 12 months' follow-up. Univariate and multivariate analyses were performed in 16 parameters. For those patients who developed an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…This adverse effect of PRM division is consistent with the literature that reports perineal wounds to be notorious for their high risk of developing surgical site infection and poor healing [27]. The most serious consequence of dividing the PRM is FI, which was recorded in 10%-12% of patients.…”
Section: Preopsupporting
confidence: 90%
“…This adverse effect of PRM division is consistent with the literature that reports perineal wounds to be notorious for their high risk of developing surgical site infection and poor healing [27]. The most serious consequence of dividing the PRM is FI, which was recorded in 10%-12% of patients.…”
Section: Preopsupporting
confidence: 90%
“…As well as the indications highlighted for stoma formation, proctectomy might also be considered in patients with strictures, and cancers forming in fistula tracks . This is not an absolute panacea, as a number of patients may still have perineal morbidity and altered pelvic function, including dyspareunia in 10% .…”
Section: Resultsmentioning
confidence: 99%
“…Proctectomy in the setting of severe fpCD is often associated with poor perineal healing, with delayed healing at or beyond 12 months in 58% of patients . A retrospective study of a cohort of 145 patients who had undergone proctectomy for Crohn's disease found persistent perianal sinus in 23% of patients, and it was associated with rectal involvement and faecal contamination of the surgical field.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of perineal sepsis pre‐operatively has been identified in previous studies [7,14] as a risk factor for an unhealed wound following proctectomy. The results of our study suggest that pre‐operative perineal sepsis (defined as a collection or fistula reported on pelvic MRI less than 1 year prior to the procedure) is not a risk factor for an unhealed wound at 12 months ( p = 0.435) or 6 months ( p = 0.515) in patients with pCD.…”
Section: Discussionmentioning
confidence: 99%
“…Historical research has identified a number of factors which have been associated with delayed or unhealed perineal wounds post-proctectomy, including gender, age, perioperative steroids, wound management, degree of contamination at operation and the presence of high fistula-in-ano [7][8][9][10][11][12][13]. More recent studies have also noted the role that pre-operative perineal sepsis plays in contributing to delayed rates of wound healing [14]. Through the consideration of current data from two specialist centres, the primary aim of this study was to determine prognostic factors associated with unhealed perineal wounds in pCD 12 months after operation.…”
Section: Introductionmentioning
confidence: 99%